2016
DOI: 10.1001/jamaoncol.2016.0447
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Breast Cancer Screening With Risk-Based and Universal Mammography Screening Compared With Clinical Breast Examination

Abstract: Compared with population-based screening for breast cancer with annual CBE, universal biennial mammography resulted in a substantial reduction in breast cancer deaths, whereas risk-based biennial mammography resulted in only a modest benefit. Compared with annual CBE, risk-based and universal mammography screening did not result in significant overdiagnosis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 27 publications
1
72
0
Order By: Relevance
“…3,54 Second, a recent 10-year populationbased cohort study of over 1.4 million asymptomatic Taiwanese women undergoing various breastcancer screening regimens showed that universal mammography screening based only on age and sex was more effective than other screening regimens (risk-based biennial mammography screening or annual CBE alone). 49 In that study, universal biennial mammography screening was associated with a 41% reduction in mortality and a rate of overdiagnosis of only 13%. In contrast, risk-based biennial mammography (pre-selecting patients according to risk profile or risk score) did not lead to any statistically significant reduction in mortality.…”
Section: Breast-screening Programmes In Hong Kong: Room For Developmentmentioning
confidence: 89%
See 2 more Smart Citations
“…3,54 Second, a recent 10-year populationbased cohort study of over 1.4 million asymptomatic Taiwanese women undergoing various breastcancer screening regimens showed that universal mammography screening based only on age and sex was more effective than other screening regimens (risk-based biennial mammography screening or annual CBE alone). 49 In that study, universal biennial mammography screening was associated with a 41% reduction in mortality and a rate of overdiagnosis of only 13%. In contrast, risk-based biennial mammography (pre-selecting patients according to risk profile or risk score) did not lead to any statistically significant reduction in mortality.…”
Section: Breast-screening Programmes In Hong Kong: Room For Developmentmentioning
confidence: 89%
“…49 Since 2004, their health service has provided free breast screening to women aged 50 to 69 years, expanded in 2010 to those aged 40 to 49 years. By 2015, about 40% of the target population participated in screening.…”
Section: Breast Screening Programmes In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have focused on ways of reducing the morbidity and mortality of breast cancer by improving early cancer detection. Breast cancer screening and early cancer detection programs include breast self-examination [7,8,9], clinical breast examination (CBE) [10,11,12,13,14,15,16,17,18,19], mammography [14,15,16,19,20,21,22,23,24], ultrasonography [14,23,24,25,26], and magnetic resonance imaging [23,27]. Although there has been constant progress in the understanding of risk factors and genetic dispositions for breast cancer [28,29,30,31,32,33,34,35,36], the majority of breast cancer cases still occur without known predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has not been shown that CBE has beneficial effects in reducing breast cancer mortality in a screening setting and this is a matter of debate [19,48,49,50], CBE is an integral part of everyday routine in clinical practice in diagnostic breast units. The aim of this study was therefore to analyze the predictive value of CBEs carried out by physicians, MTEs, and a combination of the two.…”
Section: Introductionmentioning
confidence: 99%